Peningkatan Kesehatan Masyarakat Melalui Program Pemeriksaan Lansia di Kelurahan Wonotirto Kecamatan Samboja - Aulia Fitri Andriani; Endras Amirta Hanum; Nur Afni Shafina; Linda Fatmasari; Septia Lestari; Vitrotul Kivtiyah; Zainab Inayah Al Huda (Universitas Ngudi Waluyo, 2024)
Community service in the form of free elderly examinations is carried out in Wonotirto Village RT.03 with a KKN activity scheme carried out by group 03 Incarrying ut this community service, one of the most Study,Free Elderly important aspects in human life is health, so one of the Checkup main work programs is elderly examinations, community service activities in the form of checking Kata Kunci : Kuliah uric acid, blood pressure, cholesterol, weighing, blood Kerja Nyata, Pemeriksaan Lansia Gratis sugar and administering medication from the village police midwife. Elderly (elderly) is someone who is more than 55 years old. Changes in the